10 questions: a Belgian pathologist, Peter Van Eyken, on the future of pathology. Interview by Sonia Nemolato - Peter Van Eyken (Journal of Pediatric and Neonatal Individualized Medicine, 2013)
Prof. Peter Van Eyken, a renowned Belgian pathologist, answers to the following 10 questions: 1. You are a pupil of Valeer Desmet, one of the leading liver pathologists in the world. What was it like spending so many years with him? 2. Your first research project focused on cytokeratins: how has your research changed liver biopsy interpretation in clinical practice? 3. What are the most important innovations in pathology of the last years? What is changing in your approach to histology and to cytology? 4. What is the role of pathologists in pediatric pathology? How is their relationship with pediatricians is changing? 5. How is the role of the pathologist changing in neonatal and in perinatal medicine? 6. As a young researcher, you published many articles on liver development and on bile duct atresia: did your studies change the way you approach liver biopsy interpretation in a newborn? 7. After years of involvement in kidney biopsy interpretation in adults, recently, you became involved in studies on nephrogenesis. Which is the relationship between renal development and adult kidney pathology? 8. What is your opinion on networks in medicine? Should pathology be integrated with “omic” sciences and informatics ? 9. What about the future of pathology? New techniques or new eyes in the interpretation of H&E-stained sections? What is the role of immunohistochemistry? And of of molecular pathology? 10. Could you advise young medical doctors to become pathologists? What are your suggestions?